Decreased Kernel Moisture in Medium‐Maturing Maize Hybrids with High Yield for Mechanized Grain Harvest. Issue 6 (1st November 2019) - Wang, Xingya; Wang, Xinglong; Xu, Chenchen; Tan, Weiming; Wang, Pu; Meng, Qingfeng
ABSTRACT: Kernel moisture influences harvest timing and the consequent mechanized harvest of maize ( Zea mays L.). To decrease kernel moisture, growth season (the period from sowing to physiological maturity) was usually shortened for new hybrids in China, which also resulted in lower yield. Our objective was to understand the underlying mechanism to achieve both high grain yield and low grain moisture simultaneously for new hybrids. Field experiments were conducted in 2017 and 2018 in North China Plain with three different hybrids (ZD958 as the traditional hybrid, JNK728 and DK517 as the new hybrids, and XY335 as the transitional hybrid) under three densities (60, 000, 75, 000, 90, 000 plants ha −1 ). For new hybrids, growth season was 9 to 12 d shorter than for other hybrids. Under the density of 60, 000 plants ha −1, grain yield of new hybrids was 9.1% lower compared with the traditional and transitional hybrids. When the density was increased to 75, 000 plants ha −1, grain yield of new hybrids (12.9 Mg ha −1 ) was similar or even higher. Grain moisture at physiology maturity averaged 272 g kg −1 for new hybrids, similar to the transitional hybrid and 7.5% lower compared with the traditional hybrid. The lower grain moisture mainly resulted from >30% of stover dry matter translocated to grain for new hybrids, similar to the transitional hybrid and 235.0% greater than the traditional hybrids. Furthermore, higher translocation rate was mainly from stalk in late grain‐filling stage. Our study highlighted the importance of yield improvement and the relationship between kernel moisture and dry matter translocation for new hybrids.